Cover Picture. Issue 1 (25th February 2022) - Unknown
Abstract : This cover image is based on the Review "Hippocampal neurogenesis and pro‐neurogenic therapies for Alzheimer's disease" by Zheng J. https://doi.org/10.1002/ame2.12212 . In this paper, the author reviewed recent advances in unveiling the involvement of adult hippocampal neurogenesis in Alzheimer's disease, the most common form of dementia in the elderly, and highlight the prospect of emerging pro‐neurogenic remedies including rescuing innate adult hippocampal neurogenesis, cell engraftment and glia‐neuron reprogramming. These treatments hold great potential in compensating the neuronal loss and rewiring the degenerated neuronal network in patients.